The Western Canon : The Books and School of the Ages - Bloom, Harold (Harold Irving), 1930-2019 (New York : Riverhead Books, 1994)
A study of twenty-six canonical writers details the qualities that make them literary essentials, and includes Shakespeare, Chaucer, Milton, Beckett, Tolstoy, and Freud.
Literatuurgeschiedenis - literatuurgeschiedenis